Simultaneous determination of neomycin sulfate and polymyxin B sulfate by capillary electrophoresis with indirect UV detection - Srisom P. (2014)
A simple and rapid capillary electrophoresis method, with indirect UV detection, for the simultaneous determination of neomycin sulfate and polymyxin B sulfate in pharmaceutical formulations was developed. Critical parameters such as pH, buffer composition and concentration, voltage and injection time have been studied to evaluate, how they affect responses, such as resolution and migration times. Separation was performed on a fused silica capillary with 50 μm i.d. and 27 cm total length at an applied voltage of 6 kV with a 15 mM phosphate run buffer (pH 5.0) containing 40 mM N-(4-hydroxy-phenyl)acetamide and 50 mM tetradecylammonium bromide (TTAB). The detection wavelength was set at 280 nm. Quantitative analysis was validated by testing the reproducibility of the method, giving a relative standard deviation less than 0.4 and 2.4% for the repeatability of migration time and corrected peak area, respectively. Accuracy was tested by spiking eye-ear formulations with standards and the recoveries of neomycin sulfate and polymyxin B sulfate were found to be between 97.44-103.18% and 96.85-101.68%, respectively. Linearity of neomycin sulfate and polymyxin B sulfate were obtained in the ranges of 17-682 and 24-608 μg/mL, respectively, with r2 values above 0.999. The established TLC-densitometric method was applied to evaluate the proposed CE method, and comparable results were obtained by using CE with much shorter analysis time and a small quantity of solvents consumed. The developed method is also the first report on the simultaneous determination of neomycin sulfate and polymyxin B sulfate in pharmaceutical preparations by CE. © 2006 Elsevier B.V. All rights reserved.